2016
DOI: 10.1016/j.ihj.2015.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Dental considerations in cardiovascular patients: A practical perspective

Abstract: Cardiovascular disease trends, complications, and associated therapeutics impact the dental health and treatment. Such patients require special consideration with regard to when and which dental treatment is appropriate and what precautions are required. Alertness to potential oral adverse drug reactions enables referral of patient's to his physician or cardiologist. Cardiovascular drugs are also known to have mild to potentially fatal drug interactions. Dental professionals may be the first line of defense in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 5 publications
1
26
0
2
Order By: Relevance
“…It has been shown that severe chronic microbial dental infections, endocarditis and meningitis are associated with cerebral infractions among male patients [154,155]. Additionally, research studies revealed that periodontitis has a potential role in regulating many other systemic diseases such as diabetes, respiratory disease, low birth weight, pre-term infants, other pregnancy-related issues, rheumatoid arthritis, and osteoporosis [156,157]. “Several mechanisms have been proposed to explain or support such theories, and oral lesions are indicators of disease progression, and oral cavity can be a window to overall health and body systems [156].…”
Section: Morbidity Mortality and Increase Healthcare Cost In Denmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that severe chronic microbial dental infections, endocarditis and meningitis are associated with cerebral infractions among male patients [154,155]. Additionally, research studies revealed that periodontitis has a potential role in regulating many other systemic diseases such as diabetes, respiratory disease, low birth weight, pre-term infants, other pregnancy-related issues, rheumatoid arthritis, and osteoporosis [156,157]. “Several mechanisms have been proposed to explain or support such theories, and oral lesions are indicators of disease progression, and oral cavity can be a window to overall health and body systems [156].…”
Section: Morbidity Mortality and Increase Healthcare Cost In Denmentioning
confidence: 99%
“…Additionally, research studies revealed that periodontitis has a potential role in regulating many other systemic diseases such as diabetes, respiratory disease, low birth weight, pre-term infants, other pregnancy-related issues, rheumatoid arthritis, and osteoporosis [156,157]. “Several mechanisms have been proposed to explain or support such theories, and oral lesions are indicators of disease progression, and oral cavity can be a window to overall health and body systems [156]. ” Chronic periodontitis is responsible for producing C-reactive proteins (CRP), interleukin-1b (1L-1b), interleukin-6 (1L-6), and Tumor Necrosis Factor-alpha (TNF-α) and disseminate these inflammatory mediator substances through the human body [158,159].…”
Section: Morbidity Mortality and Increase Healthcare Cost In Denmentioning
confidence: 99%
“…An angina attack can occur in the dental chair due to stress, pain and anxiety triggers. 3 Pain can be felt in the jaw, from where it can radiate to the neck and throat, so in some cases, the patient and the dentist may interpret it as toothache. If the patient experiences retrosternal pain, the procedure should be interrupted, and sublingual nitroglycerin (0.4-0.8 mg) and oxygen (3L/min) should be administered.…”
Section: Local Anesthesia In Post-myocardial Infarction Patientsmentioning
confidence: 99%
“…Cross-reactivity is triggered by the presence of oral bacteria Porphyromonas gingivalis and Tannerella forsythia, whose HSP is in 60% homologous to HSP found in mammals. 3 Thirdly, direct bacterial mechanisms (e.g., bacterial enzyme activity) contribute to the progression of cardiovascular disease. Bacterial DNA of Tanerella forsythia, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Prevotella intermedia has been found in the atherosclerotic plaque.…”
Section: Introductionmentioning
confidence: 99%
“…This inflammatory disease of the supporting tissues of teeth has long been linked to systemic diseases with high inflammatory quotient such as type 2 diabetes mellitus and CHD 5, 6. Many case-controlled, cross-sectional, and cohort studies have reported an association between periodontitis and increased cardiovascular, cerebrovascular, and peripheral artery disease, as determined by clinical disease, angiography, ultrasonography, and reduced flow-mediated dilation 7, 8…”
Section: Introductionmentioning
confidence: 99%